Utilization of social media in Learning Islamic Religion: Its Impact on Strengthening Student Outcomes and Achievements - Melly Minarti; Mariyatul Norhidayati Rahmah; Khalilurrahman Khalilurrahman; Samsir Samsir; Mardiana Mardiana (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
This study analyzes the effect of virtual entertainment stages on understudy results and accomplishments in Islamic training. Through a blended strategies approach, including overviews and meetings, information is gathered to survey understudies' utilization examples and impressions of virtual entertainment about their growth opportunities. Primer discoveries show that virtual entertainment stages offer a few benefits concerning Islamic training. First and foremost, they create a feeling of the local area and empower cooperative advancement by trading thoughts among understudies. Furthermore, these stages give simple admittance to many assets, including Islamic talks, conversations, and literary materials, improving the profundity and expansiveness of learning. Additionally, social media fosters engagement and active participation through interactive content, quizzes, and discussions, contributing to a dynamic learning environment. However, challenges associated with social media use in Islamic education are identified. These include the need for digital literacy skills and the critical evaluation of online information. The study emphasizes the importance of responsible and ethical use of social media, ensuring that the content aligns with Islamic values and principles. By shedding light on integrating social media into Islamic education, this research expands the existing knowledge on the subject. It provides valuable insights into the potential of social media platforms to improve student outcomes and achievements in studying Islamic religion. The study also underscores the significance of using social media appropriately and responsibly to ensure adherence to Islamic principles.